Structural labor market changes in France - Marcello Estev\~ao; Nigar Nargis (Institute for the Study of Labor (IZA), 2005)
France posted remarkable gains in employment in the second half of the 1990s, suggesting that, beyond cyclical factors, structural unemployment may have changed in the period. We provide a novel methodology to separate structural from cyclical labor market changes and apply it to French household level data from 1990 to 2000. We show that the equilibrium relationship between real wages and unemployment has improved significantly in France in the second half of the 1990s. Further calculations suggest that long-term unemployment will decline substantially in France with respect to its average level in the 1990s if this improved trade-off is not undone.
Keywords: D2; E2; J23; 330; employment; wages; bargaining; structural change; labor market